Resíduos sólidos : a importância do consumidor como peça-chave da logística reversa e da coleta seletiva ; um estudo de caso na cidade de Anápolis - GO - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
This thesis describes the results of a master's research on "SOLID WASTE: THE IMPORTANCE OF CONSUMER AS PART KEY OF REVERSE LOGISTICS AND SELECTIVE COLLECTION - a case study in the city of Anapolis - GO, developed in the Graduate Program in environment and Society, the State University of Goiás, UEG Campus Morrinhos in the year 2016. The objective was to analyze consumer participation in the integrated management of solid waste in the city of Anapolis, focusing on domestic solid waste (MSW) the reverse logistics of these products and the final destination for the selective collection, in accordance with Law n. 12.305 / 2010 which established the National Policy on Solid Waste, the regulatory decree n. 7,404 / 2010, which provides reverse logistics, Law 9,975 / 1999 establishing the National Environmental Education Policy, among other legal provisions pertaining to environmental matters. Methodologically work is characterized as a qualitative / descriptive research, and the data collected through the online questionnaire conducted with 100 people, field visits and observation. For analysis of the results were divided into categories - knowledge of relevant environmental preservation standards, waste types that require reverse logistics, consumer participation in the selective collection and finally an analysis of consumer awareness of this. The results reveal a worrying picture regarding consumer participation process in environmental preservation actions, as demonstrated that it is aware of the laws and is seen as the subject of this process, participate and know the environmental education, but unfortunately these actions do not go beyond the barrier of theory and thus are not implemented.
Solid waste : the importance of consumer as part key of reverse logistics and selective collection : a case study in the city of Anapolis - GO
Keywords: Resíduos sólidos; Consumidor; Coleta seletiva; Logística reversa; Solid waste; Consumer; Selective collection; Reverse logistics; SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS